(untitled) (Journal of Laboratory Animal Science, 2025)
Costus pictus, commonly referred to as the “insulin plant,” has gained interest for its antidiabetic and organ-protective properties. The objective of the study was to evaluate the claim of C. pictus leaf extract on glycaemic control, organ weights, feed intake, and biochemical parameters in a streptozotocin-induced diabetic rat model. Male Wistar rats were divided into four groups: Group 1 – Normal Control; Group 2 – Diabetic Untreated; Group 3 – Diabetic + Low-Dose C. pictus (50 mg/kg); and Group 4 – Diabetic + High-Dose C. pictus (250 mg/kg). The study was conducted as a therapeutic trial. Body weight, feed intake, organ weights, and serum biomarkers including glucose, liver enzymes, renal parameters, lipids, and proteins were monitored over six weeks. Statistical comparisons were performed using ANOVA followed by Tukey’s test. Diabetic control rats showed significant hyperglycaemia, organomegaly (notably in liver, kidney, and testis), and elevations in SGPT, ALP, urea, creatinine, and cholesterol. Treatment with C. pictus significantly reduced glucose levels by 33–37%, improved feed intake patterns, and restored liver, kidney, and testis weights toward normal. High dose treatment exhibited superior efficacy in lowering SGPT (by 76.5 U/L), ALP (by 267 U/L), urea (by 35.2 mg/dL), and creatinine (by 0.29 mg/dL). Both low and high doses of C. pictus significantly improved serum albumin and total protein levels, with high dose showing greater therapeutic benefits. C. pictus effectively ameliorates hyperglycaemia and associated hepatic and renal dysfunctions in diabetic rats, with high-dose treatment providing enhanced benefits. These findings support its potential as a plant-based adjunct in diabetes management.